The behaviours of cementitious materials in long term storage and disposal of radioactive waste : results of a coordinated research project. (IAEA-TECDOC ;, 2013)
"This publication presents the outcome of an IAEA coordinated research project that investigated the behaviour and performance of cementitious materials used for an overall waste conditioning system. The publication is intended to assist the reader in comparing cementitious systems and technologies and in reaching an informed decision based on safety, technological maturity, economics, and other local needs. It highlights the active interchange of experiences among leading research groups, which enabled them to access valuable information on the underlying science and technology of cementitious materials used in radioactive waste management. The publication can be used as a screening tool to identify cementitious systems and technologies to meet specific waste management objectives in terms of the conditioning of waste generated, the technical complexity of waste streams, the environmental impact considerations and the desired end product."--Publisher's description.